Social Support and Coping Strategies as Determinants of Quality of Life - Rajab, Muhammad; Syifa Fatimah, Thalita (International Journal of Advanced Multidisciplinary, 2023)
The purpose of this study is to establish the connection between strategy and social support coping with life quality in the context of psychosocial rehabilitation at Social Hospital. This research employs a quantitative approach. The sample size for this study includes 33 Schizophrenic Patients in psychosocial rehabilitation at Social Hospital. To select the participants, we applied a saturated sampling technique as a sampling method. Three scales, namely coping strategy, social support, and quality of life using the Likert scale, were used as the method of data collection. After examining the data, it was found that the coping strategy is positively related to life quality at a level of 0.67, while the relation between social support and life quality is also positive, with an F calculation of 2.7 and an F table of 0.7. In addition, Regression dummy using SPSS 22.0 for Windows was applied to the result of data analysis, where the correlation coefficient R = 0.814. These findings imply an association between coping strategy, social support, and life quality in psychiatric rehabilitation services in Jakarta.